2022
DOI: 10.1177/08850666221109181
|View full text |Cite
|
Sign up to set email alerts
|

Intensivist -Driven Ventilator Management Shortens Duration of Mechanical Ventilation in Coronary Artery Bypass Graft Surgery Patients

Abstract: Background Prolonged mechanical ventilation in post Coronary Artery Bypass Graft Surgery (CABG) is associated with deleterious effects including, increased ICU and hospital length of stay (LOS), infectious complications, and mortality. Standardized ventilator weaning protocols and the utilization of critical care physicians in post CABG patient care vary substantially among institutions. The purpose of this study was to evaluate if intensivist consultation in conjunction with a multidisciplinary, standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The frequency of prolonged mechanical ventilation was also reduced in the intensivist group; however, this difference was not statistically significant. These findings were likely due to earlier extubation in the intensivist group ( 17 ). In fact, we found that significantly more patients were extubated within 6 hours in the intensivist group than in the control group.…”
Section: Discussionmentioning
confidence: 94%
“…The frequency of prolonged mechanical ventilation was also reduced in the intensivist group; however, this difference was not statistically significant. These findings were likely due to earlier extubation in the intensivist group ( 17 ). In fact, we found that significantly more patients were extubated within 6 hours in the intensivist group than in the control group.…”
Section: Discussionmentioning
confidence: 94%
“…This supportive strategy has a vital role in patients undergoing major surgeries such as coronary artery bypass grafting (CABG) surgery. [ 1 2 ] Although the use of mechanical ventilation is needed to admit the patient to the intensive care unit (ICU), its absence may result in adverse consequences for such patients. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%